The Impact of Entrepreneurship Education on Entrepreneurial Intentions of University Students in Palestine - Elmobayed, Mueen Ghazi (Journal of Economic, Administrative and Legal Sciences, 2022)
The aim of this study is to find if there is an impact of the entrepreneurship education programs and courses on the entrepreneurial intentions of university’ students to new ventures in Palestine. And the study inspected the impact of Entrepreneurial knowledge on Entrepreneurial intentions.In this study, the researcher utilized a descriptive analytical method, and has used Stata program. Data has been collected via questionnaire. Sample Participants in the research comprised of students who are, at the time of the study, in the Palestinian Universities in Palestine in their last year of bachelor education of chosen faculties. These faculties are limited to Commerce (business and accounting), Engineering and Information Technology.The study revealed that there is no statistical impact of Entrepreneurial knowledge on perceived desirability, and there is no statistical impact of Entrepreneurial knowledge on perceived feasibility, while the study reported that there is no statistical impact of perceived desirability on Entrepreneurial intentions. Moreover, the study revealed that there is no statistical impact of perceived feasibility on Entrepreneurial intentions, in addition that there is no statistical impact of Entrepreneurial knowledge on Entrepreneurial intentions.Finally, the study has recommended many practical and theoretical advices to concerned academic and business organizations in Palestine.
Keywords: entrepreneurship; entrepreneurship education; entrepreneurial intentions; Entrepreneurial knowledge; perceived feasibility; perceived desirability